Pengajaran Sastra dan Politik Kebudayaan - Aprinus Salam (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
High school textbooks on literary facing serious problem, namely its curriculum didnâ€™t have clear paradigm and political-cultural basis. Its content is still subjectively-based on writer taste and still circling on technical matter. Therefore, literary lesson look like structural and cognitive memorizing. Old assumption that literary is a matter of â€œesthetical artâ€ that havenâ€™t connection with life reality is still dominant. Lesson content like this should be changed, by formulate or identifying several cultural problems in Indonesia. Based on that formulation and problems identification, literary lessonâ€™s contents packed to understand culture problems in Indonesia, therefore learning literary not only literary itself, but also become a textual ideological strategy that having vision and mission to developing Indonesia.Â